Academic Performance in Vocational Training: What Role Does Executive Function and Reading Comprehension Play? - Luque-Rojas, María Jesús; de-la-Peña, Cristina (International Journal of Assessment and Evaluation, 2023)
Academic performance is the materialization of students’ learning processes in the educational context. This research, which uses a non-experimental methodology, is a preliminary study focused on the role of executive function and reading comprehension in students’ academic performance. Its purpose is to know the relationship and prediction ability of the executive function (cognitive flexibility and verbal fluency) and reading comprehension in a sample of fifty-two higher vocational training students’ academic performances, who studied early childhood education (10% men and 90% women) with ages between 19 to 39 years old (M = 22.77, SD = 3.94). All participants took the cognitive flexibility test called CAMBIOS, the phonological and semantic verbal fluency test, and the reading comprehension instrument ICLAU (Instrumento para valorar la Comprensión Lectora en Alumnos Universitarios, [Instrument to Assess the Reading Comprehension of University Students]), and the participants participated in the registration of academic course grades in the teacher’s diary. It is a descriptive, correlational, and predictive study. The results obtained pinpoint that the executive function (cognitive flexibility and phonological and semantic verbal fluency) and the literal, critical, and appreciative dimensions correlate significantly with academic performance and predict academic achievement. The sample size limits the impact of the conclusion; thus, educational implications for students in higher vocational training are raised.
Keywords: cognitive flexibility; executive function; reading comprehension; verbal lluency; vocational training; Scopus